Cultural Studies and Media Ecology: Identifying Mass Culture and Cultural Proliferation through Javanese Pop Music on Social Media - Arina Rohmatul Hidayah; Ellyda Retpitasari (LPPM Stikosa - AWS, 2023)
The presence of Javanese pop music on social media is an interesting phenomenon to study. This phenomenon illustrates that there is a cultural transformation in society. To explore this, the researcher conducted a study using the audience reception analysis method to find out how the construction of people's meanings of the Pop Javanese phenomenon on social media, how they think the role of social media in the transformation of music that is happening and in-depth interviews with local Pop Jawa musicians, Den Juang, regarding their motives and goals for popularizing this music through social media. The data findings show that media ecology theory negates the concept of mass culture or popular culture in cultural studies. The point of emphasis in cultural studies focuses on the view that the media is a place of cultural production. Thus, there is a process of hegemony that leads to the common sense of society to accept the general